Pengembangan Petunjuk Praktikum Laju Reaksi Kimia Berbasis Green Chemistry bagi Peserta Didik SMA/MA - Mustafah, Rifa’atul Mahmudah; Auliah, Army; Husain, Halimah (Program Pasca Sarjana UNM, 2024)
This research is development research which aims to develop a green chemistry-based chemical reaction rate practicum instruction that is valid, practical and effective. The research procedure follows the 4D development model which is simplified to 3D, which consists of define, design and develop.The practicum instruction was validated by two experts. Next, it was tested in class XI IPA 3 of SMA Negeri 9 Bulukumba. The research results show that the level of validity of the Green Chemistry-based chemical reaction rate practicum instruction is declared valid and very suitable for use. Practicality is seen from: (1) the implementation of the green chemistry-based reaction rate practicum instruction is in the very practical category. Apart from that, the green chemistry-based reaction rate practicum instruction that was developed was effective in terms of the learning outcomes of class XI IPA 3 students that met the criteria for effectiveness.